HYPERBARIC OXYGEN THERAPY AS AN ADJUVANT TREATMENT IN HYDROCHLORIC ACID POISONING: A LITERATURE REVIEW - Purwo Sri Rejeki; Desi Rahmah Sari; Ismi Dian Meiliana; Dewangga Satria Sakti Kinasih; Hamidah Kurniasari (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights1. In Indonesia, 18.8% of all suicides were the result of chemical poisoning, such as using hydrochloric acid (HCl).2. Hyperbaric Oxygen Therapy (HBOT) can be used as an emergency therapy for acute pathology or as a supplementary treatment for chronic illness. AbstractBackground: Suicide is the second most common cause of death and is a major public health problem in many countries globally. Chemical poisoning, such as hydrochloric acid (HCl), accounted for 18.8% of the total suicide cases in Indonesia. Through ingestion, this acid chemical contributes as the most common cause of swallowing injuries that can adversely affect the gastrointestinal mucosal through various pathological processes, primarily through an excessive inflammatory process. On the other hand, hyperbaric oxygen therapy (HBOT) has been widely used as a non-pharmacological therapy in many diseases, although its mechanism for reducing inflammation in HCl poisoning has remained unclear. Objective: This study aimed to provide a better understanding on hyperbaric oxygen's biomolecular mechanism as a potential adjuvant therapy in HCl poisoning. Discussion: HCl poisoning causes an excessive inflammatory process, leading to tissue hypoxia indicated by increased expression of Hypoxia Inducible Factor 1 (HIF-1). Hyperbaric oxygen therapy decreases the expression of HIF-1 through activation of the HIF-1 hydroxylation pathway via prolyl hydroxylase (PDH) in the proline pathway and HIF inhibiting factor (FIH) in the asparagine pathway. Reactivating both pathways will decrease HIF-1 activity, eventually reducing the ongoing inflammatory process. In addition, HBOT also plays a role in wound healing by stimulating angiogenesis growth factors. Conclusion: Hyperbaric oxygen therapy has the potential to be used as adjuvant therapy in HCl poisoning due to its beneficial effects on reducing inflammatory mediators and wound healing.